Kidney in systemic diseases - Marta Patricia Casanova González; David Rodríguez Zamora; Aldo Luis González Pérez (Medisur)
Renal function alterant, sodium and water retention with intravascular volume expansion, and augmentation of the cardiac preload are closely related to the main causes of mortality and morbidity in patients suffering from symptomatic cardiac insufficiency. A review of the renal function alterant in congestive cardiac insufficiency and chronic liver diseases is carried out in this bibliographical revision. Important therapeutic aspects of the patients suffering from cardiac insufficiency considering its renal function alterant are also presented.